A Genome-Wide Association Study Reveals Two Genetic Markers for Chondromalacia. (September 2022) - Kim, Stuart K.; Kahn, Condor; Abrams, Geoffrey D.
Objective: It is unknown why some athletes develop chondromalacia and others do not, even when accounting for similar workloads between individuals. Genetic differences between individuals may be a contributing factor. The purpose of this work was to screen the entire genome for genetic markers associated with chondromalacia. Design: Genome-wide association (GWA) analyses were performed utilizing data from the Kaiser Permanente Research Board (KPRB) and the UK Biobank. Chondromalacia cases were identified based on electronic health records from KPRB and UK Biobank. GWA analyses from both cohorts were tested for chondromalacia using a logistic regression model adjusting for sex, height, weight, age of enrollment, and race/ethnicity using allele counts for single-nucleotide polymorphisms (SNPs). The data from the 2 GWA studies (KPRB and UK Biobank) were combined in a meta-analysis. Results: There were a total of 3, 872 combined cases of chondromalacia from the KPRB and the UK Biobank cohorts. Genome-wide significant associations with chondromalacia were found for rs144449054 in the ARHGAP15 gene (OR = 3.70 [2.32-5.90]; P = 1.4 × 10 −8 ) and rs188900564 in the MAGEC2 (OR = 2.07 [1.61-2.65]; P = 3.7 × 10 −9 ). Conclusions: Genetic markers in ARHGAP15 and MAGEC2 appear to be associated with chondromalacia and are potential risk factors that deserve further validation regarding molecular mechanisms.